Assessing the Impact of E-Commerce Platforms on Retail Consumer Goods Brand Building - Saidov, Doniyor; Saidov, Otabek; Kulmanov, Toshmurod; Mamadiyarov, Zokir; Kurpayanidi, Konstantin; Ismoilov, Botir; Makhmudov, Samariddin (International Review of Management and Marketing, 2025)
The research examines how e-commerce platform marketing attributes affect customer satisfaction while building retail brands in Uzbekistan’s developing digital economy. The research applies marketing theory to identify platform usability and information quality and delivery experience and service quality and security and customer review trust and perceived value for money as essential elements of the online marketing mix which affect consumer experience and brand perception. The research uses survey data from 1,000 Tashkent online shoppers to test and validate the relationships through Ordinary Least Squares (OLS) regression and Structural Equation Modelling (SEM). The OLS model demonstrates high explanatory power for customer satisfaction through its R2 value of 0.742. The SEM results demonstrate outstanding model performance through RMSEA = 0.000 and CFI = 1.000 and TLI = 1.000 while showing significant relationships between all attributes at P < 0.001. The study reveals that customer service quality (γ = 1.41) and product information quality (γ = 1.39) and platform usability (γ = 1.38) have the most significant impact on customer satisfaction and brand loyalty. The research demonstrates that service quality and experience design in e-commerce markets function as fundamental marketing elements which create positive customer experiences and digital brand value. The research adds value to marketing science through its digital commerce service quality extension and provides operational guidance for e-commerce managers to build customer-focused strategies and market leadership in Uzbekistan’s expanding digital retail sector.